NETWORK COOPERATION OF EDUCATIONAL ORGANIZATIONS FOR BUILDING A CULTURE OF HEALTHY AND SAFE LIFESTYLE: THEORETICAL-METHODOLOGICAL ASPECT OF VOCATIONAL STAFF TRAINING - Tatyana N. Levan (Образование и наука)
The aim of the study is to consider network cooperation as a resource of the renewal and innovative development of education.Methods. Systemization of existing practices of network partnership in the sphere of education for decision of pupils’ health protection problems; monitoring of health and physical readiness of the trainees of general educational establishments; modelling of network interaction.Results and scientific novelty. It is shown that network cooperation in the field of building a culture of healthy and safe lifestyle of pupils has a considerable potential. If educational organizations are closed to cooperation, isolated on the infrastructure in their district, city, region, the task of building a healthy lifestyle of pupils can not be solved. In general, teaching staff is unprepared for this activity and require additional preparation, methodological and methodical information materials on its realisation. The author theoretically proves and describes substantive provisions of network interaction of the educational establishments with social partners aimed at pupils’ health culture formation, which is presented as one of socialisation directions, i.e. realisation of social function of education – especially organized educational activity that is directed on development of pupils’ social competence. Thus, the model of network cooperation of educational organizations for building a culture of healthy and safe lifestyle (as one of the areas of socialization of pupils) is presented in the presented study. It is considered as a theoretical and methodological basis for the development of process of establishing partnerships of educational organizations not only with other organizations of the education system (basic, professional and additional), but also with organizations of health care, physical culture and sport, culture and recreation, and other social spheres.Practical significance. Results of research will help the pedagogical staff carrying out network interaction to present and describe own activity in a consistent manner; teachers with insufficient readiness to designing and realisation of partner communications with other organisations can use the proposed materials for vocational development; it also serves as theoretical base for formation of cognitive component of readiness for realisation of health protection function with use of network interaction resources.